Urban Heat Island Assessment using Remote Sensing Data in West Java, Indonesia: From Literature Review to Experiments and Analyses - N. Nandi; M. Dede (Indonesian Journal of Science and Technology, 2022)
Urban heat island (UHI) is a significantly increasing temperature that occurs in the urban region due to urbanization and anthropogenic activities. The UHI represents environmental quality decrease and able to change a microclimate in the long term. It phenomenon can be estimated using multi-temporal remote sensing imagery data. This study aims to analyze the spatial dynamics of UHI in the urban region of West Java from 1998 to 2018. We only used remote sensing data from different datasets. Information of land-surface temperature is extracted from Landsat-5 TM and Landsat-8 OLI images using radiative transfer equation which validated using MODIS data in the same period. This study showed that UHI intensity in the urban region of West Java reach 5.11oC in 2018. For 20 years, the land-surface temperature increased to 4.44oC. The UHI distribution is concentrated in the central business district, industrial area, harbor, terminal, airport, and traffic jam zone. The UHI significantly increased in Depok and Cimahi, which are known as satellite cities for the surrounding megapolitan (Jakarta and Bandung Raya). This model has high validity result with a correlation value of 0.74. The UHI management is important to strengthen urban resilience in the environmental field through green open space, green belts, roof gardens, land use and land cover formal direction, and the use of high albedo materials to build construction.